Evaluation of the Jordanian experience in blended/alternating distance education (Darsak Platform) and in attendance to confront the Corona pandemic during the years 2020-2021 challenges, positives, negatives - Hazeen, Ahmad Mosleh (Journal of Educational and Psychological Sciences, 2022)
The research aimed to evaluate the Jordanian experience in blended/alternate education during the Corona pandemic; The researcher used the descriptive analytical approach during the Corona pandemic between 2020-2021; The first topic began to talk about traditional and electronic education, and the pros and cons of each, to the challenges and shortcomings facing e-learning in Jordan. The second topic dealt with blended education in general. Its concept, benefits and features, and the requirements for its success in the public education environment, including human and technological needs. This came as a prelude to the third topic, which talked about the main topic of research; It is the Jordanian experience in blended education in the time of Corona, the stages it went through, and the evaluation of each of them, starting with the stage of distance education, then the stage of blended education, and ending with the stage of "Darsak" platform, and the research ended with presenting the most important results that were reached, such as: Blended education combines Among the advantages of traditional education and e-learning, and putting them together in one framework, ensuring the building of an educational model and an effective learning method, which is characterized by efficiency in providing academic content to students. The Corona pandemic has greatly affected education worldwide, and Jordan was one of the countries affected by the repercussions of the pandemic. Corona, which was reflected in education in it, education in Jordan was able to keep pace with the developments that have occurred to it; As a result of the Corona pandemic; By using all available means and tools; For the continuation of distance learning in homes, the Ministry of Education in Jordan launched the “Darsak” platform, which was concerned with building bridges of communication between students and teachers, and providing video lessons for students; to help them complete their studies.
Keywords: COVID-19; jordan; Darsk platform